L’éloquence de la chaire à l’époque romantique : le cas de Lacordaire et de Lamennais - Sukiennicka, Marta (Studia Romanica Posnaniensia, 2015)
This paper considers French ecclesiastical rhetoric in the Romantic era, focusing on Lacordaire’s and Lamennais’ contrasting views on the role of eloquence in religious discourse. It argues that Lacordaire, despite employing secular language in his Conférences remains a classicist religious orator, whereas Lammenais expresses his deep distrust of the spoken word and condemns eloquence, turning to letters and political discourse. The comparison of the two concepts can be seen as an exemplification of the transition from littérature-discours to littérature-texte, a general phenomenon in the French Romantic literature as described by Alain Vaillant.